Case Report: Severe Eosinophilic Asthma Associated With ANCA-Negative EGPA in a Young Adult Successfully Treated With Benralizumab - Ricciardi, Luisa; Soler, Daniel Griscti; Bennici, Alessandra; Brunetto, Silvia; Pioggia, Giovanni; Gangemi, Sebastiano (Frontiers in Pharmacology, 2022)
Background: Traditionally, Eosinophilic Granulomatosis with Polyangiitis (EGPA) has been treated with systemic corticosteroids and immunosuppressants. In recent years, therapeutic efforts have been directed towards targeting eosinophils which represent a major player in the pathogenesis of EGPA. In 2017 the Food and Drug Administration (FDA) approved mepolizumab, a humanized monoclonal antibody targeting interleukin 5 (IL-5) which reduces the production and survival of eosinophils, already used to treat severe eosinophilic asthma, for the management of EGPA. Benralizumab is a humanized monoclonal antibody that targets the IL-5 receptor and is indicated in the treatment of severe eosinophilic asthma. Case description: We describe the case of a young female with a positive history of severe eosinophilic asthma associated with EGPA, treated successfully with benralizumab.